Aromaticity and antiaromaticity : basics and applications /: basics and applications. (2022) - Solà, Miquel; Boldyrev, Alexander I; Cyrański, Michał K (Michał Ksawery); Krygowski, Tadeusz Marek; Merino, Gabriel
No abstract available